Association between Physical Activity, General Health and Burden of Dementia Caregivers - E, Dimakopoulou; P, Sakka; M, Karydaki; E, Margioti; M, Theodorelou (Journal of Sports Research, 2018)
Most caregivers do not engage in physical activity programs despite evidence that physical exercise improves general health and relieves symptoms of depression, anxiety and stress. The aim of the study is a) to investigate the amount of physical activity of caregivers in everyday life, b) to examine the reasons of limited participation in physical activities and c) to find out if limited participation in physical activity affects their general health. Fifty three (n=53) caregivers (59.04±12.76 yrs) were recruited by a Dementia Day Care Center. A caregiver questionnaire was designed to obtain information on basic demographics, living habits and current care details (hours of care, etc). The Greek version of PASE questionnaire was used to measure the amount of physical activity undertaken by caregivers. Caregiver burden was assessed via the Greek version of the validated Zarit burden interview and general health was investigated via the Greek version of General Health Questionnaire (GHQ-28). All data were analyzed by using SPSS, version 22. The majority of caregivers are daughters or wives. The current sample had a PASE mean score of 168.0±87.46. Differences in PASE score were found between occupational status (F=6.210, p=0.001) and living arrangements (F=3.882, p=0.05). No differences were found in PASE score between different levels of burden (F=1.058, p=0.376). PASE score was not related to GHQ28 scores. High correlations were found between ZBI and GHQ28 total (r=0.71, p=0.001) and ZBI and GHQ28 four subscales (somatic: r=0.62, p=0.001, anxiety-insomnia: r=0.66, p=0.001, social dysfunction: r=0.54, p=0.002, severe depression: r=0.44, p=0.003). ZBI was also correlated with years of care (r=0.38, p=0.004) and hours of care/day (r=0.40, p=0.003). The most frequent barriers to physical activity cited by caregivers were their living arrangements and their occupational status. In addition, burden was not cited as a significant barrier.